A comparative analysis of caries and fluorosis among cities with and without public water supply fluoridation in São Paulo State, Brazil - Moimaz, Suzely Adas Saliba [UNESP]; Costa, Adriana Cristina Oliva [UNESP]; Silva, Ligia Prandi da [UNESP]; Saliba, Orlando [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Araújo, Kátia Santos (FapUNIFESP (SciELO), 2010)
Purpose: This population-based, cross-sectional study aimed to record the DMFT index for 12 year-old children with dental caries and fluorosis levels in cities with and without public water supply fluoridation. Methods: From the 101 municipalities belonging to the Health Regional Department XV (DRSXV-SJRP) of the São Paulo state in the Southeast region of Brazil, 85 cities were selected after exclusion of those with incomplete data and less than ten years of fluoridation treatment in 2004. The criteria adopted for the assessment of dental caries and fluorosis levels were based on the guidelines published in the WHO Manual 4th edition. The data were analyzed using Fisher’s exact tests at a significance level of 5%. Results: The prevalence of caries in 12 year-old children had no significant association with fluoridated water, and was considered “moderate” and “high” in cities without fluoridation and “low” and “moderate” in cities with fluoridation. A significant association was found between water fluoridation and fluorosis (P=0.001), but not between water fluoridation and the DMFT index (P=0.119). Conclusion: The prevalence of fluorosis was related to water fluoridation in this study. However, fluorosis was also observed in non-fluoridated cities, which may result from fluoride intake through other sources.

Objetivo: Este estudo transversal, de base populacional, teve por objetivo medir os índices CPO-D aos 12 anos e de fluorose em municípios com e sem fluoretação da água de abastecimento público. Metodologia: De 101 municípios pertencentes à Divisão Regional de Saúde XV – São José do Rio Preto (DRS-XV), Estado de São Paulo, na região Sudeste do Brasil, foram selecionados 85 municípios, sendo excluídos os aqueles que apresentaram dados incompletos e que possuíam menos de dez anos de fluoretação em 2004. Os critérios adotados para avaliação de cárie e fluorose foram baseados no manual da OMS 4ª edição. Os dados foram submetidos à análise estatística através do teste Exato de Fisher, ao nível de significância 5%. Resultados: A prevalência de cárie aos 12 anos não teve associação significativa com a água fluoretada e foi considerada “moderada” e “alta” em municípios sem fluoretação e “baixa” e “moderada” nos municípios com fluoretação. A água fluoretada teve associação significativa com fluorose (P=0,001) mas não com o índice CPO-D (P=0,119). Conclusão: Houve associação entre prevalência de fluorose e água fluoretada, mas a fluorose também foi observada em municípios sem fluoretação, possivelmente pelo flúor existente nas diversas fontes de ingestão.
Análise comparativa de cárie e fluorose entre municípios paulistas com e sem fluoretação das águas de abastecimento público
Keywords: Dental caries; Fluorosis; Dental; Fluoridation; Cárie dentária; Fluorose dentária; Fluoretação